Identifying the Factors that Attract Ciputra and Petra Christian University Students as a New Target Market to Come to Xiang Fu Hai of Vasa Hotel Surabaya on Weekdays - Magdalena Patricia (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
Xiang Fu Hai is a Chinese restaurant of Vasa Hotel Surabaya which has started its business from 2017. Even though Xiang Fu Hai has already established for 2 years, Xiang Fu Hai has a low number of customers on weekdays. However, on weekends, this Chinese restaurant is always full of customers. Xiang Fu Hai cannot depend on the existing customers and has to find a new target market which is university students. A marketing research for a new target market is needed to know the factors that can attract them to come to Xiang Fu Hai. The marketing research help Xiang Fu Hai to create offers which match with the university students needs and demand, and the offers can run effectively and successfully. By having a marketing research, the company has the base to make right offers, so they will not waste much time and money for trials and errors. Keywords: customer, new target market, university students, marketing research, offers.